Cultural factors influencing Japanese nurses’ assertive communication. Part 1: Collectivism - Mieko Omura (2018)
© 2018 John Wiley & Sons Australia, Ltd Culture influences the way health-care professionals communicate with each other and their ability to relate to colleagues in an assertive manner. Cultural barriers can also make it difficult for nurses to speak up even when they have concerns about patient safety. An understanding of the potential impact of cultural factors is therefore needed when developing assertiveness communication training programs. This paper presents the findings from a study that explored Japanese nurses’ perceptions of how culture and values impact assertive communication in health care. Semistructured interviews with 23 registered nurses were undertaken, and data were analyzed using directed content analysis. Two major themes were identified: collectivism and hierarchy/power. In the present study, we discuss the cultural values related to collectivism that included four categories of “wa” (harmony), “uchi to soto” (inside and outside), implicit communication/ambiguity, and “nemawashi” (groundwork). The findings highlight the impact of culture on nurses’ assertive communication behaviors and can be used to inform the design of culturally-appropriate assertiveness communication training programs for Japanese nurses working both within their own country or internationally.